A combined approach for the treatment of lateral and posterolateral tibial plateau fractures. Issue 10 (October 2016) - Zhang, Peng; Lian, Kejian; Luo, Deqing; Huang, Zunxian; Li, Teng; Lin, Dasheng
Abstract: Introduction: The treatment of tibial plateau fractures involving the lateral and posterolateral column is a demanding and fine surgical challenge. The purpose of this study was to evaluate the safety and clinical efficacy of combined approach for the treatment of lateral and posterolateral tibial plateau fractures. Methods: A prospective study was performed in 17 patients with lateral and posterolateral tibial plateau fractures between January 2009 and December 2012. There were 12 males and 5 females with a mean age of 40 years. All of them received dual-plate fixation through the combined approach, with the patients in a floating position. The combined approaches included a conventional anterolateral approach and an inverted L-shaped posterolateral approach. Operation time, intraoperative blood loss, fracture healing time, Hospital for Special Surgery (HSS) knee score, knee flexion and extension range of motion, and complications were recorded to evaluate treatment effects. Results: There were no intraoperative complications related to this technology. Mean operation time was 144 min with a mean intraoperative blood loss volume of 233 mL. The mean follow-up was 23 months. All 17 patients had good postoperative fracture healing. Mean union time was 12 weeks. At the final follow-up, the average HSS score was 92.5, with the average knee flexion of 125° and an average knee extension of 2°. Two patients had complications in postoperative incisions with aseptic fat liquefaction. After thorough debridement, second-stage wounds healing were achieved. No neurovascular injury occurred. No collapse of reduced articular surface was detected. Conclusions: The combined approach with dual-plate offers direct and complete surgical exposure and provide an effective method for the treatment of lateral and posterolateral tibial plateau fractures.